The Effect Of Peer Social Support On Quarter-Life Crisis In Final-Year Students In Medan City - Sihombing, Tesa Kristin Floren; Brahmana, Karina Meriem Beru (STABN RADEN WIJAYA WONOGIRI, 2023)
This study aims to evaluate the Influence of Peer Social Support on Quarter-Life Crisis in Final-Year Students in Medan City. Based on the results of research conducted on 158 final-year students in Medan City, it can be concluded that there is a significant influence between peer social support and quarter-life crisis. This study uses a simple linear regression analysis method to test the hypothesis and determine how much fluence the independent variable (peer social support) has on the dependent variable (quarter-life crisis). The results of the analysis show that the significance value is 0.000 (<0.05), so the alternative hypothesis (H₁ ) is accepted. This means that there is a real influence of peer social support on quarter-life crisis in final-year students. The coefficient of determination (R Square) value of 0.221 indicates that 22.1% of the variation in quarter-life crisis can be explained by peer social support. In other words, the higher the level of social support students receive from their peers, the lower the level of quarter-life crisis they experience. Conversely, low social support has the potential to worsen the crisis condition. The Adjusted R Square value of 0.216 strengthens the consistency of the model even with corrections to the number of variables used.